Survey: A wide and deep neural network with their implementation - et. al., Akmam Majed Mosa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The notion concerning a neural community capable concerning transcribing ethnical composition has long gone beyond a list in accordance with turning into an almost insignificant task. Neural networks started out abroad as like simply a mathematical concept, no longer something that may want to remain performed together with the technological know-how degree of the time, however above period the thoughts grew and the science eventually caught up. ANNs commenced including an assignment via McCullogh and Pitts whichever described up to expectation sets concerning easy devices (artificial neurons) could operate entire viable logic operations or hence stay capable regarding normal computation. In 1985, Rumelhart, McClelland, yet Hinton determined a powerful study regime that allowed them to educate ANNs together with various black units. Actually, flagrant neural networks (DNNs) are awfully utilized because of extraordinary features and have performed state-of-the-art performances.in it record review an overview present day concerning the research touching DNNs’ implementations are presented. As because the large awful neural networks, we showed the purpose for the appearance of this kind regarding network, the features, the architecture over these networks, the learning strategies used, as differentiates this networks beside the traditional networks. After the suggestion of an algorithm of fast learning for deep networks through 2006, the deep learning methods have induced regularly-growing study attention for the reason of their intrinsic ability to overcome the disadvantage of classical algorithms conditional on manually-prepared characteristics. Deep learning strategies have further been discovered to be proper for huge data examination with prosperous applications to computer vision, pattern recognition, etc. In this paper, we consider several architectures of widely-used deep learning with their functional applications. A modern summary is presented on some deep learning architecture, wide Deep Neural Networks Implementations, traditional neural network, embedding vector. Various kinds of deep neural networks are viewed and modern forwards are compiled. Employment of deep learning methods on remarkable chosen fields also analyzed.